Especiação de níquel e cobalto em águas estuarinas do Amazonas empregando voltametria de redissolução - Trindade, Cristina Ramos (2020)
The estuaries are defined as the region of mixing fresh water from the river and sea water. They are characterized as dynamic ecosystems inserted in a complex hydrographic network. Among the estuaries, the Amazon River estuary stands out as one of the most important in the world. The present study aimed to carry out the complete speciation of nickel and cobalt in the Amazon estuary. Water samples were collected during the scientific expedition GEOTRACES M147 on board the research ship Meteor (Germany). A total of 106 samples were collected, which were subdivided into 2 groups: filtered (using 0.2 μm membranes) and unfiltered (>0.2 μm). The determination of Ni (II) and Co (II) was carried out simultaneously in the presence of dimethylglyoxime (DMG) 0.1 mol L-1 as complexing agent by adsorptive cathodic stripping voltammetry (AdCSV). During the study it was observed the formation of Ni complexes with DMG with high stability constant (log K >17), thus allowing the determination of “reactive” Ni bound to labile organic complexes (log K <17) with the dissolved organic matter (DOM). The same behavior was not observed for “reactive” dissolved Co species. This fact can be explained due to the formation of strong organic complexes with Co in the dissolved phase, which are more stable than Co complexes with DMG. Two important processes were observed along the estuary: removal and addition of Ni and Co species. The decrease of Ni and Co species may be linked to biological absorption in regions of medium salinity (~13-20). The phenomenon of addition was also observed in the high salinity mixing zone (>23). The addition of dissolved (<0.2 μm) and particulate (>0.2 μm) species of Ni and Co was also observed, which were observed in high salinity samples (~ 30-35). Thus, it can be concluded that Ni and Co species enter the estuarine zone predominantly associated with particles (~70-90%), mainly related to the Amazon River region. Colloidal species (0.015-0.2 μm) of Ni were also observed in the mixing zone. However, most of the dissolved Ni is transported in the estuarine mixing zone as soluble species (<0.015 μm).